Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
(a) The second stone hit after 2.91 seconds
(b) The initial velocity of the second stone must be 15.8 m/s vertically downward.
(c) The velocity of each stone when they reach the water is: First stone : -30.7 m/s Second stone: -34.5 m/s
The height and velocity of the stones can be calculated using the following equations:
y = y0 + v0 · t + 1/2 · g · t²
v = v0 + g · t
Where:
y = height at time "t".
y0 = initial height.
v0 = initial velocity.
t = time.
g = acceleration due to gravity (-9.81 m/s² considering the upward direction as positive).
v = velocity at time "t".
a) If we place the origin of the frame of reference on the water, then, the height of both stones when they hit the water will be 0. Using the equation of height for the first stone, we can obtain the time when the height is 0:
y = y0 + v0 · t + 1/2 · g · t²
0 = 50.0 m -1.91m/s · t - 1/2 · 9.81 m/s² · t²
0 = 50.0 m - 1.91 m/s · t - 1.6 m/s² · t²
Solving the quadratic equation:
t = 2.91 s
The two stones hit the water 2.91 s after the release of the first stone.
b) The second stone reaches the water in (2.91 s - 1.00 s) 1.91 s after released (remember that it was released 1.00 s after the first stone but both reached the water simultaneously). Then, using the equation of height, we can obtain the initial velocity knowing that at t = 1.91 s, y = 0:
y = y0 + v0 · t + 1/2 · g · t²
0 = 48.0 m + v0 · 1.91 s - 1/2 · 9.81 m/s² · (1.91 s)²
(-48.0 m + 1/2 · 9.81 m/s² · (1.91 s)²) / 1.91 s = v0
v0 = -15.8 m/s
The initial velocity of the second stone must be 15.8 m/s vertically downward.
c) We have to use the equation of velocity for each stone. We already know the time when the stones reach the water and the initial velocities:
First stone:
v = v0 + g · t
v = -2.18 m/s - 9.81 m/s² · 2.91 s
v = -30.7 m/s
Second stone:
v = v0 + g · t
v = -15.8 m/s - 9.81 m/s² · 1.91 s
v = -34.5 m/s
The velocity of each stone when they reach the water is:
First stone : -30.7 m/s
Second stone: -34.5 m/s
Therefore, the velocity of the first and second stones are -30.7 m/s and -34.5 m/s.
To know more about velocity, refer: https://brainly.com/question/17003580
#SPJ4
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.